2008
DOI: 10.1109/tdmr.2008.2002345
|View full text |Cite
|
Sign up to set email alerts
|

Reliability Evaluation for Copper/Low-$k$ Structures Based on Experimental and Numerical Methods

Abstract: Bump shear is widely used to characterize the interfacial strength of Cu/low-k structures. In this paper, the blanket low-k structure was used to evaluate the reliability and strength of Cu/low-k structures based on experiment and finite-element modeling technique. The objectives of this paper are to determine the critical stress parameters for low-k interfaces with different low-k structures, to understand the failure mechanism, and to improve low-k structure reliability by optimizing some parameters. In this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…They developed the FEM to predict the EM voids, in which three mechanisms including EM, thermo-migration(TM) and stress migration(SM) were considered [22].…”
Section: Trend Of Interconnect Modelingmentioning
confidence: 99%
“…They developed the FEM to predict the EM voids, in which three mechanisms including EM, thermo-migration(TM) and stress migration(SM) were considered [22].…”
Section: Trend Of Interconnect Modelingmentioning
confidence: 99%
“…Previous studies have indicated that stress and the corresponding inelastic strains are localized at the edge of the solder/pad interface leading to crack initiation and fracture of the interconnection [3][4][5][6]. The location of stress concentration at the edge of the solder/IMC interface plane during solder ball shear push test is illustrated in Fig.…”
Section: B Stress Evolution During Solder Ball Shear Push Testmentioning
confidence: 99%
“…In this respect, numerous numerical models based on finite element (FE) method have been developed and examined [1][2][3][4][5][6][7][8][9][10][11][12]. The accuracy of FE models is largely dependent on the accuracy of the input model geometry, correct loading and boundary conditions prescribed, and physically sound constitutive equations employed for the package materials being modeled.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature distribution can strongly affect the interconnect resistance, and, consequently, the signal integrity of circuits can be degraded. Furthermore, low-k materials are generally used to reduce the effect on interconnect time delay, crosstalk and dynamic power consumption [8,9]. However, because of the poor thermal conductivity of such materials, most of the *Corresponding author (email: fire5water@hotmail.com) Joule heating produced by the interconnects on every level cannot be transmitted to the heat sink.…”
mentioning
confidence: 99%